Nuclear F-actin counteracts nuclear deformation and promotes fork repair during replication stress - Lamm, Noa; Read, Mark N; Nobis, Max; Van Ly, David; Page, Scott G; Masamsetti, V Pragathi; Timpson, Paul; Biro, Maté; Cesare, Anthony J (Nature cell biology, 2020)
Filamentous actin (F-actin) provides cells with mechanical support and promotes the mobility of intracellular structures. Although F-actin is traditionally considered to be cytoplasmic, here we reveal that nuclear F-actin participates in the replication stress response. Using live and super-resolution imaging, we find that nuclear F-actin is polymerized in response to replication stress through a pathway regulated by ATR-dependent activation of mTORC1, and nucleation through IQGAP1, WASP and ARP2/3. During replication stress, nuclear F-actin increases the nuclear volume and sphericity to counteract nuclear deformation. Furthermore, F-actin and myosin II promote the mobility of stressed-replication foci to the nuclear periphery through increasingly diffusive motion and directed movements along the nuclear actin filaments. These actin functions promote replication stress repair and suppress chromosome and mitotic abnormalities. Moreover, we find that nuclear F-actin is polymerized in vivo in xenograft tumours after treatment with replication-stress-inducing chemotherapeutic agents, indicating that this pathway has a role in human disease.